Ease of Communication as Mediating the Effect of Instagram Social Media on Purchase Intentions on the Marketplace - Wisnalmawati Wisnalmawati; Agus Sasmito Aribowo; Dipo Hardi Dewantoro; Preya Alvita Yasmine; Olinda da Conceicao (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2021)
ABSTRACT. Marketing using digital media on the internet has become a necessity in the era of industrial technology 4.0. The Covid-19 pandemic has caused a shift in consumer behavior. Usually face to face changes to online shopping. UMKM Kuncup Seruni is a company that manufactures herbs and herbs from agricultural and plantation products. MSME Sri Rejeki is engaged in processing salak fruit products into various types of food, drinks, and snacks. The two MSME partners have produced many products. MSME's marketing reach is only local and promotions only rely on MSME exhibitions and showrooms that are available in the hope that consumers will come directly to the location. After the COVID19 pandemic, the number of visitors decreased drastically so that sales also decreased. The purpose of this study is to analyze the influence of Instagram social media on purchase intentions on Marketplace and analyze the influence of Instagram social media on purchase intentions on Marketplace mediated by the ease of communication. The novelty that emerged in this research is to develop the ease of communication so that the ease of communication is a very important concept to increase purchase intention. The research method related to the unit of analysis of this research is the consumers of UMKM Seruni and Sri Rejeki. The sample is 60 consumers, the sampling technique uses accidental, data collection uses a questionnaire (google form), conducts validity and reliability tests. The analysis technique uses the model of Structural Equation Modeling with PLS (Partial Least Square). Data analysis is descriptive and quantitative analysis. The results showed that there was no significant and significant effect of Instagram social media on purchase intentions on the Marketplace. The influence of Instagram social media on purchase intention is mediated by the ease of communication